Decadal fCO2 trends in global ocean margins and adjacent boundary current‐influenced areas. Issue 17 (9th September 2017) - Wang, Hongjie; Hu, Xinping; Cai, Wei‐Jun; Sterba‐Boatwright, Blair
Abstract: Determination of the rate of change of sea surface CO2 fugacity (f CO2 ) is important, as the f CO2 gradient between the atmosphere and the ocean determines the direction of CO2 flux and hence the fate of this greenhouse gas. Using a newly available, community‐based global CO2 database (Surface Ocean CO2 Atlas Version 3 coastal data set) and a newly developed statistical method, we report that the global ocean margins (within 400 km offshore, 30°S–70°N) f CO2 temporal trends on decadal time scales (1.93 ± 1.59 μatm yr −1 ) closely follow the atmospheric f CO2 increase rate (1.90 ± 0.06 μatm yr −1 ) in the Northern Hemisphere but are lower (1.35 ± 0.55 μatm yr −1 ) in the Southern Hemisphere, reflecting dominant atmospheric forcing in conjunction with different warming rates in the two hemispheres. In addition to the atmospheric f CO2 forcing, a direct warming effect contributes more to f CO2 increase in the western boundary current‐influenced areas, while intensified upwelling contributes more to f CO2 increase in eastern boundary current‐influenced areas. Key Points: f CO2 temporal trend increases from south to north in ocean margins and boundary current‐influenced areas Ocean margin f CO2 responds to thermal and nonthermal effects differently in boundary current‐influenced areas